(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this paper we consider the effect of edge contraction on the Dominance Contraction Survey on Theory and Applications of Graphs. In order to reduce the (total) dominance number of a graph, we determine a minimum number of borders that must be contracted. We show that the two numbers for each diagram are at most three. In light of this outcome, graphs are graded and defined by their (total) number of dominance contractions The next article includes the notion of dominating planar graphs, linked graphs, edge dominance of paths, associated graph cycles and few characteristics. Likewise, we have extended our research on inverse graphic and domain-based applications.